Luteimonas chenhongjianii, a novel species isolated from rectal contents of Tibetan Plateau pika (Ochotona curzoniae). Issue 5 (20th April 2020) - Zhang, Gui; Lai, Xin-He; Yang, Jing; Jin, Dong; Pu, Ji; Xiong, Yanwen; Yang, Caixin; Dong, Kui; Huang, Ying; Luo, Xuelian; Lu, Shan; Xu, Jianguo
Abstract : Two Gram-stain-negative, strictly aerobic, bright-yellow-pigmented and rod-shaped bacteria (strains 100069 and 100111 T ) with a single polar flagellum were isolated from the rectal contents of plateau pika ( Ochotona curzoniae ). Based on the results of nearly full-length 16S rRNA gene sequence and phylogenetic analyses, strains 100069 and 100111 T belong to the genus Luteimonas, and are closest to Luteimonas rhizosphaerae 4-12 T (98.02 % similarity), Luteimonas aestuarii B9 T (97.8 %) and Luteimonas terrae THG-MD21 T (97.74 %). The DNA G+C contents of these two isolates were 68.30 mol% and 68.29 mol%, respectively. The highest average nucleotide identity (ANI) value between strain 100111 T and its closely related species was 83.34 %, well below the threshold of 95–96 %. The major cellular fatty acids were iso-C11 : 0, iso-C15 : 0 and iso-C17 : 1 ω9. Polar lipid content was dominated by diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, an unidentified phospholipid and an unidentified lipid. Ubiquinone-8 (Q-8) was the predominant respiratory quinone. These two isolates grew optimally at 35–37 °C, pH 7.0–8.0 and with 1.0 % (w/v) NaCl. The results of ANI analysis and other characteristics obtained from our polyphasic study showed that strains 100069 and 100111 T represent a novel species in genus Luteimonas, for which the name Luteimonas chenhongjianii sp. nov. (type strain 100111 T =DSM 104077 T =CGMCC 1.16429 T ) is proposed.